Immunosuppression Reversal Nanovaccines Substituting Dendritic Cells for Personalized Cancer Immunotherapy - Chen, Hu; Cheng, Hongwei; Liang, Xiaoliu; Cai, Shundong; Liu, Gang (Frontiers in Immunology, 2022)
Although immunotherapy has paved a new avenue for cancer treatment, inadequate immune response often executes suboptimal therapeutic effects. In general, an effective immune response undergoes presentation of antigen by antigen-presenting cells, proliferation and differentiation of lymphocytes, and attack of cancer cells by cytotoxic T lymphocytes (CTLs). The antigen self-presentation and immunosuppression reversal (ASPIRE) nanovaccine derived from dendritic cells provides a simplified and immune deregulated procedure for immunotherapy profiting from its orientable peculiarity. By integrating major histocompatibility complex class I (MHC-I) molecules into present specific epitopes and co-delivering anti-PD-1 antibody and B7 costimulatory molecules through the programmed biomimetic synthesis, the ASPIRE nanovaccine demonstrates a milestone in personalized cancer immunotherapy.